2004
DOI: 10.1152/japplphysiol.01272.2003
|View full text |Cite
|
Sign up to set email alerts
|

Soluble gas exchange in the pulmonary airways of sheep

Abstract: We studied the airway gas exchange properties of five inert gases with different blood solubilities in the lungs of anesthetized sheep. Animals were ventilated through a bifurcated endobronchial tube to allow independent ventilation and collection of exhaled gases from each lung. An aortic pouch at the origin of the bronchial artery was created to control perfusion and enable infusion of a solution of inert gases into the bronchial circulation. Occlusion of the left pulmonary artery prevented pulmonary perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These include inhibition of protein kinase C, calcium release from sarcoplasmic reticulum, and voltage-dependent calcium channels [37-39]. In vivo , such mechanisms require that the anesthetic diffuse from lumen through the airway wall to reach the smooth muscle layer [40,41], as shown in Figure 1. This process is mediated by the relative partition coefficients for these agents, with a larger ratio between airway smooth muscle and gas indicating a greater likelihood of diffusion from airway lumen to ASM [41].…”
Section: Bronchodilation With Volatile Anestheticsmentioning
confidence: 99%
“…These include inhibition of protein kinase C, calcium release from sarcoplasmic reticulum, and voltage-dependent calcium channels [37-39]. In vivo , such mechanisms require that the anesthetic diffuse from lumen through the airway wall to reach the smooth muscle layer [40,41], as shown in Figure 1. This process is mediated by the relative partition coefficients for these agents, with a larger ratio between airway smooth muscle and gas indicating a greater likelihood of diffusion from airway lumen to ASM [41].…”
Section: Bronchodilation With Volatile Anestheticsmentioning
confidence: 99%
“…Experimentally, increases in bronchial blood flow in excised and whole animal preparations 38,43 produce increases in soluble gas elimination. Theoretical calculations 1,5,19 align with these experimental findings.…”
Section: Methodsmentioning
confidence: 99%
“…Because neither argument has been proven conclusively, an experimental investigation was performed to directly assess this assumption. That study used a novel aortic pouch preparation to alter bronchial blood flow (a major factor in airway gas exchange) and demonstrated that changes in bronchial blood flow affected the excretion of highly blood-soluble gases (e.g., ether and acetone) more than low blood-soluble gases (e.g., SF 6 and ether) 38 . But this study could not conclusively resolve the effect of airway gas exchange on MIGET.…”
Section: Introductionmentioning
confidence: 99%
“…Then, this dissolved fraction flows to the lower digestive tract where it is absorbed into the blood or passed out with the faecal material. Studies have reported diffusion of SF 6 into the lungs from venous blood (Schimmel et al, 2004), suggesting that SF 6 absorption takes places from the digestive tract. As long as the SF 6 is excreted via the breath and not stored in the body, this route of excretion per se could not be responsible for the association between RR of SF 6 and the CH 4 emission estimates.…”
Section: Sf 6 Tracer Technique and Ch 4 Emission Estimatesmentioning
confidence: 99%